1991
DOI: 10.1111/j.1651-2227.1991.tb11937.x
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Monomorphic Ventricular Tachycardia in a 4‐Year‐Old Boy with Toxic Multinodular Goiter

Abstract: A case of toxic multinodular goiter associated with repetitive monomorphic ventricular tachycardia (VT) is reported. A 4-year-old boy was found to have asymptomatic VT. When treatment with antiarrhythmic agents turned out to be ineffective, thyrotoxicosis was suspected due to the rapid enlargement of the left thyroid gland and associated thyroid function studies. A diagnosis of toxic multinodular goiter was made on the basis of subsequent scintigraphy and ultrasonography. Treatment with antithyroid drugs and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…These cases have additional common clinical features such as no family history of sudden cardiac death, no history of syncope attack, and no identifiable causes accounting for VT or Vf, which are thus idiopathic. Interestingly, in four cases found in the literature (10,11,13,14), no ventricular arrhythmias were recorded after the thyroid function was controlled, and therefore, the patients needed only temporary medical treatments for ventricular arrhythmia and did not require the implantation of an ICD. The disappearance of Vf as a result of the improvement of thyroid function was also seen in Patient 1 and Patient 2 in the present study.…”
Section: Retrospective Survey Of the Medical Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases have additional common clinical features such as no family history of sudden cardiac death, no history of syncope attack, and no identifiable causes accounting for VT or Vf, which are thus idiopathic. Interestingly, in four cases found in the literature (10,11,13,14), no ventricular arrhythmias were recorded after the thyroid function was controlled, and therefore, the patients needed only temporary medical treatments for ventricular arrhythmia and did not require the implantation of an ICD. The disappearance of Vf as a result of the improvement of thyroid function was also seen in Patient 1 and Patient 2 in the present study.…”
Section: Retrospective Survey Of the Medical Recordmentioning
confidence: 99%
“…Ischemic heart disease is another cause of Vf seen in patients with thyrotoxicosis, probably because thyroid hormone is known to increase cardiac oxygen consumption (2). Thus, it is even rarer for thyrotoxic patients not accompanying hypokalemic periodic paralysis to develop Vf without ischemic heart disease (10)(11)(12)(13)(14) or with stable coronary disease (15). We present three cases of GD complicated by idiopathic Vf without hypokalemic periodic paralysis or ischemic heart disease.…”
Section: Introductionmentioning
confidence: 97%
“…In the first case, at a 4-year-old boy admitted because of febrile convulsions, asymptomatic, monomorphic ventricular tachycardia was noted and responded to anti-thyroid treatment after anti-arrhythmic drugs were deemed ineffective [6]. The second case involved coarse ventricular fibrillation reported to be triggered by palpation of the thyroid gland during surgery while the patient was under anesthesia [5].…”
Section: Discussionmentioning
confidence: 97%
“…In literature, it has been demonstrated that thyroid disorders can cause life-threatening ventricular arrhythmias without any underlying cardiac disease [5,6] but underlying mechanism for ventricular arrhythmias is unclear. In thyrotoxicosis, there is usually a decrease in systemic vascular resistance, an increase in cardiac output, heart rate, and systolic blood pressure, an enhanced left ventricular contractility, ejection fraction, and blood volume and a global impairment of diastolic heart performance [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…But, nodular forms may also be associated to rhythmic troubles (10). Other etiologies can have the same impact on heart function, but they are less common than in adults.…”
Section: Discussionmentioning
confidence: 98%